PERGESERAN POLA PINJAMAN TRADISIONAL KE PINJAMAN ONLINE: PERSPEKTIF HUKUM TERHADAP PENGARUHNYA PADA KESETARAAN EKONOMI DI INDONESIA - Ririn, Stio (Ensiklopedia Education Review, 2025)
Abstract: The digital transformation in the financial sector, particularly the shift from traditional lending to online lending (P2P lending), has introduced new dynamics into Indonesia's economic landscape. The Financial Services Authority Regulation (POJK) No. 77/POJK.01/2016 on Peer-to-Peer Lending serves as the primary legal framework governing and overseeing the operations of online lending platforms. This study aims to analyze the impact of this shift on economic equality in Indonesia, with a legal perspective on the implementation of POJK No. 77/POJK.01/2016. The research adopts a normative juridical approach with an analysis of relevant regulations, including literature review and comparison with international practices. The findings reveal that, while POJK No. 77/POJK.01/2016 provides a clear legal framework for P2P lending operations, challenges remain in terms of consumer protection and supervision, which may affect the success of online lending in promoting economic equality. While online lending has the potential to increase financial inclusion for underserved populations, there are still legal gaps that can be exploited by providers to the detriment of consumers. Therefore, there is a need for regulatory updates and strengthening to ensure that online lending contributes to equitable access to financial services without exacerbating economic disparities.Keywords: Online Lending, POJK No. 77/POJK.01/2016, Economic Equality, Consumer Protection, Financial Inclusion, Fintech Regulation.